Heat and drought-resistant wheat varieties in Pakistan help farmers combat climate change stress and is success of physiological breeding approach - CGIAR Research Program on Wheat (2018)
The stress of climate change on wheat production means farmers urgently need more heat and drought tolerant varieties. An innovative approach by WHEAT scientists, combining genetic diversity with physiological and molecular breeding and bio-informatic technologies, has resulted in several successful outcomes, including three lines of wheat varieties specifically bred for increased tolerance to heat and drought in Pakistan. The Pakistan Agricultural Research Council has taken on certified seed multiplication more than 100,000 Pakistani farmers currently grow one or more of the 3 varieties.